Development of Electronic Student Worksheets (E-LKPD) with Problem Based Learning (PBL) Model on Impulse And Momentum Teaching Materials - Yovita Ina Palang; Handoyo Saputro (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to produce a product in the form of physics E-LKPD with a Problem Based Learning model on impulse and momentum teaching materials according to the syntax and to determine the feasibility and student responses to the product. This type of research is research and development developed by Sugiyono that is simplified into eight stages. The subjects of this study consisted of two physics education lecturers and class X students of SMK Tamansiswa Jetis. The data analysis technique is descriptive statistical analysis. The results of this study are E-LKPD with Problem Based Learning Model on impulse and momentum teaching materials which were developed according to its syntax. Based on the results of the feasibility assessment analysis, it is known that the E-LKPD with the PBL model on impulse and momentum teaching materials shows the percentage of Very Good (SB) 71% and Good (B) 29%. While the results of the analysis of student responses, the percentage of Strongly Agree (SS) 20%, Agree (S) 73% and Disagree (TS) 7% on the components of material coverage, presentation, language and contextual.